O07.1 Multiple lineages of multiresistant shigella in australia. (14th July 2019) - Williamson, Deborah; Ingle, Danielle; Easton, Marion; Chow, Eric; Seemann, Torsten; Kwong, Jason; Fairley, Christopher; Kirk, Martyn; Howden, Benjamin; Chen, Marcus
Abstract : Background: In developed countries, the burden of shigellosis is either in returning travellers, or in men who have sex with men (MSM). Here, we combine genomic data with comprehensive epidemiological data on sexual exposure and travel to describe the spread of multidrug-resistant Shigella lineages in an urban centre in Australia. Methods: We undertook a population-level study of all cultured Shigella isolates in the state of Victoria, Australia between 1 January 2016 through to 31 December 2018. Antimicrobial susceptibility testing, whole genome sequencing (WGS) and bioinformatic analysis of 610 Shigella isolates was performed on all isolates, and long-read sequencing was performed on representative isolates. Risk factor data on travel and sexual exposure were collected through enhanced surveillance forms or by interview. Results: Rates of antimicrobial resistance were high in both S. sonnei and S. flexneri, particularly to ciprofloxacin and azithromycin. There were strong associations between antimicrobial resistance, phylogeny and epidemiology; specifically, two major MSM-associated lineages were identified, a S. sonnei lineage and a S. flexneri 2a lineage. Of concern, the majority of isolates within the S. sonnei MSM-associated lineage harboured mutations associated with reduced susceptibility to recommended oral antimicrobials, namely ciprofloxacin, trimethoprim-sulfamethoxazole and azithromycin. Long-read sequencing demonstrated global dissemination of multidrug-resistant plasmids across Shigella species and lineage, but predominantly associated with MSM isolates. A global analysis demonstrated the presence of these plasmids in Shigella from both Europe and South-East Asia. Conclusion: Our contemporary data highlight the ongoing public health threat posed by multidrug-resistant Shigella, both in Australia and globally, and further highlights the 'collateral damage' caused by azithromycin. Urgent multidisciplinary public health measures are required to interrupt transmission and prevent infection. Disclosure: No significant relationships.